Severe hypertriglyceridemia associated with hyperviscosity syndrome in an adult patient with acute pyelonephritis [Akut piyelonefritli erişkin bir hastada hipervizkozite ile seyreden ciddi hipertrigliseridemi] - (:unkn) unknown (My University, 2007)
We report a case of severe hypertriglyceridemia associated with hyperviscosity syndrome in an adult patient with acute pyelonephritis. A 38-year-old-female patient presented with headache, weakness, fever, and chest discomfort. In the case the diagnosis of acute pyelonephritis suggested by fever, tenderness in left costovertebral angles on the palpation, leukocytosis, and bacteria detectable in Cram-stained unspun urine. On hospital admissions routine laboratory examinations showed a severe hyperlipidemia with serum triglyceride levels of 6910 mg/dl. A antibiotic therapy with quinolone was initiated and resulted in a prompt decrease in the serum lipid levels. In conclusion our case report suggest that during infection plasma triglyceride levelsi increase and hyperviscosity syndrome may ocur in the patient with hypertriglyceridemia type IV.
Keywords: Acute pyelonephritis; Hypertriglyceridemia; Hyperviscosity syndrome